Safari Books Online webcast: Building iPhone apps with HTML, CSS, and JavaScript. - Stark, Jonathan, 1968- (Safari Books Online, 2012)
"It's a fact - if you know HTML, CSS and JavaScript, you already have the tools you need to develop your own iPhone apps! You can design and build apps for the iPhone and iPod Touch with existing open source web technologies without using Objective-C or Cocoa. Mobile apps that work on multiple platforms are the wave of the future. Learn about these new technologies from a recognized expert by watching this recorded webcast provided by Safari Books Online! You will learn to convert your product into a native iPhone app using the free PhoneGap framework. Releasing your product as a web app first will help you find, fix and test bugs much faster than if you went straight to the App Store with a product built with Apple's tools. Author Jonathan Stark shows you how to: - Build iPhone apps with tools you already know how to use - Learn how to make an existing website look and behave like an iPhone app - Add native-looking animations to your web app using jQTouch - Take advantage of client-side data storage with apps that run even when the iPhone is offline - Hook into advanced iPhone features - including the accelerometer, geolocation and vibration - with JavaScript - Submit your applications to the App Store with Xcode The future of mobile development is clearly web technologies like CSS, HTML and JavaScript. Leverage your existing web development skills to build native iPhone applications using these technologies."--Resource description page.